Which UTAUT Elements Drive Mobile Banking Adoption in Indonesia, Despite Security and Trust Concerns? - Fachrudin , Khaira Amalia; Amin , Syajarul Imna Mohd; Hamid , Siti Ngayesah Ab; Latifah S , Siti; Lubis, Muhammad Arif (Journal of Ecohumanism, 2025)
Mobile banking is easier and more practical than traditional banking, but problems with cyber security and trust exist. The purpose of this study was to investigate the factors that influence Indonesian consumers’ intention to use mobile banking. This study integrated the unified theory of acceptance and use of technology model with security and trust and uses education level as a moderating variable. This study involved 482 Indonesian participants who had used mobile banking, with primary data obtained through a structured questionnaire. Data analysis was carried out using partial least squares structural equation modeling. The results showed that at a significance level of 5%, performance expectancy, effort expectancy, social influence and system quality had a positive and significant effect on consumers’ intention to use mobile banking. Meanwhile, security and trust had a positive but insignificant effect. Education level was able to moderate only the effect of social influence on consumers’ intention to use mobile banking. The implication of this study is that policymakers can create important strategies. In addition, the government can create policies that support a sense of security for users.